Fiscal Policy and Occupational Employment Dynamics - Falko Jüßen; Christian Bredemeier; Roland Winkler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We document heterogeneity in occupational employment dynamics in response to government spending shocks. Employment rises most strongly in pink-collar occupations, while employment in blue-collar occupations is hardly affected. We develop a business-cycle model that explains the heterogeneous occupational employment dynamics as a consequence of differences in the short-run substitutability between labor and capital services across occupations.
Keywords: E62; E24; J21; J23; 330